Analysis of the main components of LSPN based on broadly targeted metabolomics technology - Qin, Feng; Chen, Yuyong; Wang, Dada; Li, Jingui; Zhu, Shanyuan (Frontiers in Plant Science, 2025)
IntroductionThis study aimed to (1) establish a broadly targeted metabolomics workflow to evaluate batch-to-batch variability in Panax notoginseng-derived Panax notoginseng stem/leaf-derived oral liquid (LSPN) preparations, (2) identify critical process-induced metabolite differences (e.g., saponin degradation products), and (3) correlate these differences with pharmacopoeial quality markers (e.g., Rg1/Rb1 ratios).MethodsOur hypothesis was that thermal extraction parameters would significantly alter saponin profiles, detectable via orthogonal metabolomic approaches (HPLC-MS/MS, PCA).ResultsThe results showed a strong positive correlation (pearson correlation coefficient >0.92) between triterpenoid saponins in LSPN-S and LSPN-C. Thirty-eight triterpenoid saponins were detected, of which 11 were up-regulated, 5 were down-regulated, and the other 22 had less than a two-fold difference in content. Ginsenoside Rb3 showed a modest but significant downregulation in LSPN-S (fold change = 0.45, VIP = 1.11) compared with LSPN-C.DiscussionMetabolomic analysis confirmed the suitability of the selected Panax notoginseng stems/leaves as raw materials, with comprehensive characterization of LSPN’s primary components.